Innovative Learning in English Language Teaching and Improving Communication Skills through Technology at SMA Tribhakti Tanggulangin - Satunggale Kurniawan; Muhammad Afifi Rahman; Yuventius Sugiarno (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study aims to explore the effectiveness of innovative technology-based learning in improving students' communication skills in English learning at SMA Tribhakti Tanggulangin. The background of this study is based on the low level of student engagement and communication skills in conventional learning. The innovative learning implemented integrates technology such as learning applications, interactive videos, and online discussion platforms to create a dynamic and collaborative learning environment. The research method uses a descriptive quantitative design with a quasi-experimental approach, involving 60 grade XI students who are divided into experimental and control groups. The results showed that the experimental group that participated in technology-based learning experienced significant improvements in speaking and listening skills, compared to the control group that used traditional methods. In addition, students in the experimental group reported higher levels of engagement, felt more confident in communicating, and were more motivated in learning English. This study also identified that obstacles such as internet access and devices were still obstacles, although the benefits of using technology were much more dominant. The conclusion of this study confirms that English learning that combines innovative and technological approaches can have a positive impact on improving students' communication skills significantly and enjoyably.